Tax Planning, Corporate Governance and Financial Performance of Selected Quoted Non-Financial Companies in Nigeria (2007–2018) - Olayiwola, John; Okoro, Stephanie (Organizations and Markets in Emerging Economies, 2021)
This study examines the interactive effect of tax planning and corporate governance on the financial performance of 50 non-financial quoted companies in Nigeria between 2007 and 2018. The study sample that covers 9 sectors was selected purposively through stratified random sampling. Data used were collected from the audited annual reports and accounts of selected quoted companies in Nigeria and fact books published by the Nigeria Stock Exchange. A system GMM was employed to estimate the dynamic models, and results show that ownership structure (OS) and capital intensity (CI) exerted a significant and positive impact on the returns on assets. This implies that OS plays a significant role to ensure that CI triggers an increase in the return on assets of the quoted Nigerian companies. However, board diversity and thin capitalization wielded a significant and negative influence on return on assets. This study thus recommends that companies should put in place a strong corporate governance mechanism that will monitor, check and balance tax planning activities and strategies adopted by the management of quoted companies in Nigeria.